2015
DOI: 10.1097/mpg.0000000000000864
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Ω‐3 Supplementation on Fatty Acids and on Visual and Cognitive Development

Abstract: Omega-3 LC-PUFA dietary supplement during pregnancy and lactation influenced the mother and newborn's fatty acid profile and nervonic acid content but did not show effects on visual and cognitive/psychomotor development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 40 publications
0
51
0
1
Order By: Relevance
“…As we have previously reported (Hurtado et al . ), our mother supplementation with omega 3 LC‐PUFA during the gestation and lactation increased the percentage of DHA and other fatty acids of the omega‐3 series in different cell compartments, both in the mother (placenta, plasma, erythrocyte membrane and milk) and in their neonates (plasma and erythrocyte membrane), reason why we have not included information about the mother or neonate fatty acids profile in the current study.…”
Section: Discussionmentioning
confidence: 93%
“…As we have previously reported (Hurtado et al . ), our mother supplementation with omega 3 LC‐PUFA during the gestation and lactation increased the percentage of DHA and other fatty acids of the omega‐3 series in different cell compartments, both in the mother (placenta, plasma, erythrocyte membrane and milk) and in their neonates (plasma and erythrocyte membrane), reason why we have not included information about the mother or neonate fatty acids profile in the current study.…”
Section: Discussionmentioning
confidence: 93%
“…Six studies investigated a possible association between milk levels of L-PUFAs and child mental development using the Mental Developmental Index (MDI) of the Bayley Scales of Infant and Toddler Development, which evaluates several aspects related to toddler cognitive development, including memory, habituation and problem solving, through the assignment of a score directly proportional to the quality of the toddler's performance. Half of the studies did not find a significant association between milk L-PUFAs levels and MDI scores (Hurtado et al, 2015;Jensen et al, 2005;Westerberg et al, 2011). In contrast, three studies found a significant association between high total milk fat content (Agostoni et al, 2001) or DHA milk levels (Makrides et al, 2009) and high MDI scores; and a trend for an association between high levels of ω-3 L-PUFAs and ω-3/ω-6 L-PUFAs ratio and high MDI scores (Guxens et al, 2011).…”
Section: Toddlerhood Lipidsmentioning
confidence: 89%
“…However, the n ‐3 PUFA, DHA and EPA levels obtained in erythrocytes membrane compare favourably to studies of n ‐3 PUFA supplementation in humans (Hurtado et al . ). Thus, final assessment of the potential therapeutic value of neonatal n ‐3 PUFA supplementation is based on physiological outcomes.…”
Section: Discussionmentioning
confidence: 97%